2019
DOI: 10.1021/acsearthspacechem.9b00158
|View full text |Cite
|
Sign up to set email alerts
|

Astrochemistry as a Tool To Follow Protostellar Evolution: The Class I Stage

Abstract: The latest developments in astrochemistry have shown how some molecular species can be used as a tool to study the early stages of the solar-type star formation process. Among them, the more relevant species are the interstellar complex organic molecules (iCOMs) and the deuterated molecules. Their analysis give us information on the present and past history of protostellar objects. Among the protostellar evolutionary stages, Class I protostars represent a perfect laboratory in which to study the initial condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 169 publications
(493 reference statements)
0
40
0
Order By: Relevance
“…Recently, DC 3 N has been detected in some low-mass cores (see e.g., Refs. [9], [15]) and in a sample of 15 highmass star-forming cores [16]. The latter work, based on the spectroscopic results presented in this paper, suggests that DC 3 N is enhanced in the cold and outer regions of star-forming regions, likely indicating the initial deuteration level of the large-scale molecular cloud within which star formation takes place.…”
Section: Introductionmentioning
confidence: 56%
“…Recently, DC 3 N has been detected in some low-mass cores (see e.g., Refs. [9], [15]) and in a sample of 15 highmass star-forming cores [16]. The latter work, based on the spectroscopic results presented in this paper, suggests that DC 3 N is enhanced in the cold and outer regions of star-forming regions, likely indicating the initial deuteration level of the large-scale molecular cloud within which star formation takes place.…”
Section: Introductionmentioning
confidence: 56%
“…By studying the prototypical Class I protostars, SVS13-A, Bianchi et al (2017aBianchi et al ( , 2019a reported a decrease of deuteration of methanol, thioformaldehyde, and formaldehyde with respect to what is found towards Class 0 objects. With the results obtained for the four Class I sources in our sample, we can verify what is found in SVS13-A.…”
Section: Deuterium Fractionationmentioning
confidence: 95%
“…Class I protostars, with a typical age of 10 5 yr are a bridge between Class 0 protostars (∼10 4 yr), where the bulk of the material that forms the protostar is still in the envelope and the Class II protoplanetary disks (10 6 yr). Class I sources have recently begun to be chemically characterized through spectral surveys at millimeter wavelengths to search for interstellar complex organic molecules, small organics and deuterated species (Öberg et al 2014;Bergner et al 2017;Bianchi et al 2017a;Bergner et al 2019;Bianchi et al 2019aBianchi et al , 2020Le Gal et al 2020). Therefore, we are still far from concluding whether Class I protostars are also a bridge from a chemical point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn stresses the importance of investigating Class I objects, a sort of bridge between the prototellar phase and the protoplanetary disks around Class II young objects. Several projects focused on the chemical complexity of Class I objects have been recently performed, mainly focusing the attention on interstellar small or complex (with at least 6 atom) organic molecules and/or deuteration using both singledishes and interferometer (see e.g., Öberg et al 2014;Bianchi et al 2017;Bergner et al 2017Bergner et al , 2019Bianchi et al 2019aBianchi et al ,b, 2020Le Gal et al 2020;Yang et al 2021).…”
Section: Introductionmentioning
confidence: 99%